Periprosthetic joint infection and heterotopic ossification after total hip arthroplasty: systematic review and meta-analysis - Łukasz Pulik; Paweł Łęgosz; Edyta Brzóska; Bartosz Mierzejewski; Iwona Grabowska; Maria A. Ciemerych; Robert Hube (BMC Musculoskeletal Disorders)
Abstract This meta-analysis addresses the relationship between infection developing after total hip arthroplasty (THA) and heterotopic ossification (HO). To critically assess the limitations of existing literature we screened for full-length peer-reviewed research articles listed in PubMed, Embase, and Web of Science over the past 20 years (2004–2024). The following search terms and Boolean operators were used: heterotopic ossification AND infection AND (hip replacement OR hip arthroplasty). A total of 14 articles were identified that describe periprosthetic joint infection (PJI) and HO after THA. Data summarized from 6 studies suitable for further meta-analysis yielded a cumulative sample size of 753 observations, with 186 recorded events of HO. The pooled RR was estimated at 2.22 (95% CI: 1.00 to 4.91, p = 0.0497), suggesting a more than twofold risk of HO compared to the group without PJI. Basic research findings support the hypothesis that bacterial pathogen-associated molecular patterns (PAMPs) can lead to osteogenesis through a toll-like receptor (TLR) and nuclear factor kappa B (NF-κB) pathway. Together, these results suggest that during revisions following THA for presumed non-septic reasons, the presence of HO warrants consideration for infection, as there is a potential heightened risk of pathologic ossification induced by PAMPs.